Docosahexaenoic acid inhibits TNF-α-induced osteoclast formation and orthodontic tooth movement through GPR120 - Ma, Jinghan; Kitaura, Hideki; Ogawa, Saika; Ohori, Fumitoshi; Noguchi, Takahiro; Marahleh, Aseel; Nara, Yasuhiko; Pramusita, Adya; Kinjo, Ria; Kanou, Kayoko; Kishikawa, Akiko; Ichimura, Atsuhiko; et al. (Frontiers in Immunology, 2023)
Docosahexaenoic acid (DHA) is an omega-3 fatty acid that has a range of positive impacts on human health, including anti-inflammatory effects and inhibition of osteoclast formation via G-protein-coupled receptor 120 (GPR120). Orthodontic force was reported to induce tumor necrosis factor-α (TNF-α) expression, which activates osteoclast differentiation during orthodontic tooth movement (OTM). The aim of this study was to investigate the influence of DHA on TNF-α-induced osteoclast formation and OTM in vivo. We examined osteoclast formation and bone resorption within the calvaria of both wild-type (WT) and GPR120-deficient (GPR120-KO) mice injected with phosphate-buffered saline (PBS), TNF-α, TNF-α and DHA, or DHA. DHA inhibited TNF-α-induced osteoclast formation and bone resorption in WT mice but had no effect in GPR120-KO mice. OTM experiments were performed in mouse strains with or without regular injection of DHA, and the effects of DHA on osteoclast formation in the alveolar bones during OTM were examined. DHA also suppressed OTM in WT but not GPR120-KO mice. Our data showed that DHA suppresses TNF-α-induced osteoclastogenesis and bone resorption via GPR120. TNF-α has considerable significance in OTM, and therefore, DHA may also inhibit TNF-α-induced osteoclast formation and bone resorption in OTM.